1996
DOI: 10.1074/jbc.271.42.25928
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C α Expression Is Required for Heparin Inhibition of Rat Smooth Muscle Cell Proliferation in Vitro and in Vivo

Abstract: Heparin is a complex glycosaminoglycan that inhibits vascular smooth muscle cell (SMC) growth in vitro and in vivo. To define the mechanism by which heparin exerts its antiproliferative effects, we asked whether heparin interferes with the activity of intracellular protein kinase C (PKC). The membrane-associated intracellular PKC activity increased following stimulation of cultured rat SMCs with fetal calf serum and was suppressed by heparin in a time- and dose-dependent manner. Heparin acted through a selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…In addition, overexpression of PKCδ [35] or PKCα [36] inhibits SMC proliferation as well. It is interesting to note that activation of PKC also stimulates SMC proliferation [45]. The different PKC isozymes are thought to have distinct functions regarding the phosphorylation of specific substrate proteins [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of PKCδ [35] or PKCα [36] inhibits SMC proliferation as well. It is interesting to note that activation of PKC also stimulates SMC proliferation [45]. The different PKC isozymes are thought to have distinct functions regarding the phosphorylation of specific substrate proteins [46].…”
Section: Discussionmentioning
confidence: 99%
“…Rat-1 cells were transiently transfected in serum-free DMEM with 10 M antisense (AS) or scrambled (SC) oligonucleotides for 2, 4, 6, or 9 days with new pulses every 48 h. AS and SC oligonucleotides were synthesized at the Molecular Resource Center Synthesis Facility (The University of Tennessee, Memphis, TN). These oligonucleotides have been used by other investigators to specifically down-regulate PKC␣ (Herbert et al, 1996), PKC␦ (Pessino et al, 1995; modified for rat isoform), PKC⑀ (Traub et al, 1997; modified for rat isoform), and PKC , or were designed against the translation initiation site (nucleotides 136 -155) of PKN (Mukai and Ono, 1994). The sequences used were as follows: PKC␣ AS, 5Ј-CAGCCATGGTTCCCCCCAAC-3Ј; PKC␣ SC, 5ЈCCAGTCACTCGCACCATCGC-3Ј; PKC␦ AS, 5Ј-ACGGTGCCAT-GATGGA-3Ј; PKC␦ SC, CGAGTAGTTACAGCGG-3Ј; PKC⑀ AS, 5Ј-CATGAGAGCAGATCTGACCT-3Ј; PKC⑀ SC, 5Ј-AACGCATAACTCG CTTGAGG-3Ј; PKC AS, 5Ј-CTGCTGCCGGAGCCCCGA-3Ј; PKC SC, CCGAGAGCCGCCGTCGTC; PKN AS, 5Ј-AGGTTCACTCTGCA CGGCGT-3Ј; and PKN SC, 5Ј-AGTATTCCGGTCGAGCCCTG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, PKC␣ did not control the front polarization of the MTOC in medial SMCs, suggesting different regulatory pathways in the two cell types. Others have shown that PKC␣ activity increases between 6 and 48 hours after balloon injury in vivo, preceding migration of SMCs to the intima, 31 and that PKC inhibition attenuates SMC migration. 32 Other PKC isoforms are expressed in SMCs (including the ␤, ␦, , and isoforms) 31 ; however, our experiments with selective PKC inhibitors demonstrated that none of these other isoforms affect rear polarization of neointimal SMCs.…”
Section: Discussionmentioning
confidence: 99%